PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR SISWA MATERI PANTUN PADA MATA PELAJARAN BAHASA INDONESIA - Harahap, Asriana; Harahap, Nurul Khafifah (DIRASATUL IBTIDAIYAH, 2023)
This research was motivated by the low learning outcomes of class V students at SD Negeri 0301 Sokopan in the Indonesian language subject, pantun material due to the teacher's ineffectiveness in using innovative learning models in the learning process. This research aims to determine the significant influence of using the Make a Match learning model on student learning outcomes in rhyme material in class V of SD Negeri 0301 Sosopan. This type of research is descriptive quantitative. The research population was all class V students, totaling 20 students. The sampling technique used was total sampling. Based on data analysis, it was obtained that (1) An overview of the use of the Make a Match learning model in rhyme material in class V of SD Negeri 0301 Sosopan obtained student response questionnaire results in the high category with a score of 90%. (2) Description of student learning outcomes for pantun material in class V of SD Negeri 0301 Sosopan using the Make a Match learning model, obtained an average score of 43 in the "D" category and the average score after using the Make a Match learning model obtained an average score of average of 85.66 with category "A". (3) There is a significant influence of the Make a Match learning model on student learning outcomes for pantun material in class V of SD Negeri 0301 Sosopan. This is proven by the one sample test, it is known that the significant value (2-tailed) is 0.00, where the significant value is 0.000.05. Keywords: Make a Match Learning Model; Learning Outcomes; Pantun.